Government Communication in the Digital Era in Branding The Soul of Java as the Wonosobo Regency Slogan - Dwian Hartomi Akta Padma Eldo; Sri Rahayu (Journal of Dialogos, 2024)
The role of the Government in conveying information today has challenges, one of which is the digital era which must be utilized properly. This research aims to see and analyze the Digital Communication carried out by the Wonosobo Regency Government in Branding the soul of Java as the slogan of Wonosobo Regency. This is very important to study because it needs to be seen how far the effectiveness achieved in this regard. The method used was a descriptive qualitative approach with interviews as one of the data collection techniques in addition to direct observation. Informants were selected based on their suitability for understanding digital communication and Wonosobo the soul of Java branding strategies. The results showed that the Wonosobo Regency Government utilizes social media in carrying out its digital communication, and the platforms used are Instagram, Facebook, YouTube, and TikTok. While the effectiveness in utilizing social media is still not optimal, this is because Wonosobo people are not familiar with social media as a means of government communication and also Wonosobo people mostly work as farmers who do not have much activity on social media.